2021
DOI: 10.1186/s13046-021-01861-6
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCDC183-AS1 acts AS a miR-589-5p sponge to promote the progression of hepatocellular carcinoma through regulating SKP1 expression

Abstract: Background Hepatocellular carcinoma (HCC) is a common type of malignant human cancer with high morbidity and poor prognosis, causing numerous deaths per year worldwide. Growing evidence has been demonstrated that long non-coding RNAs (lncRNAs) are closely associated with hepatocarcinogenesis and metastasis. However, the roles, functions, and working mechanisms of most lncRNAs in HCC remain poorly defined. Methods Real-time quantitative polymerase c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…For instance, circRNA microarray analysis showed that hsa_circ_0016070 is correlated with pulmonary arterial hypertension in patients with chronic obstructive pulmonary disease [ 18 ]. circDNMT3B overexpression reduces the retinal acellular capillary number and attenuates visual impairment in diabetic rats [ 19 ]. In the present study, the expression of circ-UBAP2 was overexpressed in the vitreous humor of DR patients and HG-treated hRMECs, which was consistent with a previous study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, circRNA microarray analysis showed that hsa_circ_0016070 is correlated with pulmonary arterial hypertension in patients with chronic obstructive pulmonary disease [ 18 ]. circDNMT3B overexpression reduces the retinal acellular capillary number and attenuates visual impairment in diabetic rats [ 19 ]. In the present study, the expression of circ-UBAP2 was overexpressed in the vitreous humor of DR patients and HG-treated hRMECs, which was consistent with a previous study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-589-5p was predicted and confirmed to be a potential target of circ-UBAP2. To date, miR-589-5p has been mainly investigated in oncogeneses, such as hepatocellular carcinoma [ 19 , 20 ], renal cell carcinoma [ 21 ], and laryngocarcinoma [ 22 ]. However, it has not been sufficiently explored in DR. Zou et al [ 23 ] confirmed that miR-589-5p targets the oxidative damage gene XPC-rs2229090 C allele in the age-related cataract (ARC), which might increase the risk of ARC.…”
Section: Discussionmentioning
confidence: 99%
“…MYOSLID promotes the progression of osteosarcoma through the miR-1286/RAB13 axis [ 59 ], and MYOSLID plays a key role in stomach neoplasm through the miR-29c-3p-mcl-1 axis [ 60 ], but it has not been reported in CC. CCDC183-AS1 enhances hepatocellular carcinoma progression by regulating SKP1 expression via MIR-589-5P [ 61 ]. The miR-3127-5p/E2F7 axis increases CC cell proliferation and migration, and LINC00174 plays a role in this process [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…For miRNA, reverse transcriptions were performed using the Mir-X miRNA First-Strand Synthesis Kit (Takara, Japan). Real-time qPCR was performed as described previously [ 19 ]. U6 and GAPDH were used as endogenous controls for the detection of circRNA, miRNA, and mRNA expression, respectively.…”
Section: Methodsmentioning
confidence: 99%